Pineapple Leaf Fiber Painting (Ananas Comosus): An Ecopreneurship Education Perspective - Hadi Alhail; Nicolaus Ramli Bachtiar Sijabat; Riski Juliandri Tambunan; Rionaldo Tamba; Achmad Zairin; Adek Cerah Kurnia Azis (Gorga : Jurnal Seni Rupa, 2025)
This research aims to explore the ability of teachers and students of SMA Negeri 1 Sipahutar in processing pineapple leaf fibers into paintings based on ecopreneurship education and equipping them to manage pineapple leaf waste independently as a medium for learning crafts. The problem faced is that the concept of ecopreneurship has not been integrated into the 2013 Curriculum so that students' work has not been oriented towards sustainability and economic value. The research uses a descriptive qualitative approach with the Participatory Action Research (PAR) model through the stages of planning, training, mentoring, and evaluation. Data were obtained through observation, interviews, documentation, and document studies, analyzed with the Spradley model. The results show that this program can make partners gain knowledge in exploring painting using pineapple leaf fibers based on ecopreneurship at SMAN 1 Sipahutar by utilizing animated videos and guidebooks that have been given to partners. Partners have applied independently in the classroom in processing pineapple leaf fibers into paintings in learning crafts through online training so that they have the opportunity to become jobseekers. With the online training on making pineapple leaf fiber paintings through animated videos and guidebooks, in the future partners can develop local potential to achieve the goals of craft learning with the implementation of the 2013 curriculum. The program has received a positive response from teachers and school principals regarding the idea of using pineapple leaf fiber as an exploration material in painting. This program supports the purpose of learning craft while opening up opportunities for environmentally friendly entrepreneurship in schools.